Estimation and Comparative Evaluation of Serum Iron, Copper, Zinc and Copper/Zinc Ratio in Oral Leukoplakia, Submucous Fibrosis and Squamous Cell Carcinoma - Apeksha R Balpande; R S Sathawane (Wolters Kluwer Medknow Publications, 2010)
Higher incidence of oral cancer and precancer in Indian population necessitates in depth probing of various etiological and contributory factors for its early diagnosis and prognosis. In the present study serum iron, copper, zinc levels and Cu/zn ratio were estimated in control and study groups [oral leukoplakia (OL), oral submucous fibrosis (OSMF), oral squamous cell carcinoma (OSCC)]. Estimation of these trace elements was done by colorimetric method using semi automated analyzer. Serum iron level and Cu/Zn ratio were significantly reduced while serum copper was increased significantly in OL, OSMF, and OSCC. The comparison of these trace elements between study groups was also found to be significant. Thus, assessment of Cu, Zn, Fe and Cu/Zn ratio can be used as auxiliary test to clinicopathological diagnosis and prognosis of oral precancer and cancer.